(untitled) (Proceedings of the Global Public Health Conference, 2021)
Coronavirus Disease 2019 (COVID-19) has changed people’s habits nowadays. Every aspect of daily living was affected, mainly by people’s health, economy, politics, national defense for the macro problems, and the micro problems such as the social living of human beings and psychological aspect of an individual. COVID-19 brings difficult conditions for almost all of the people in the world. The hard condition can make an individual become stressed and have to adapt to the situation by doing the coping strategies. This research aims to find the profile of stress rate, then the source of the stress condition, type of coping managements and coping have been done as coping strategies that have been done by Universitas Airlangga Students in COVID-19 pandemic condition. This research is descriptive research conducted on Universitas Airlangga students around September – October 2020. This cross-sectional research was to collect the information by using a questionnaire with a total of 45 questions. The number of samples is 121 respondents with criteria as an active Universitas Airlangga student in bachelor degree. The information was collected then analyzed with the SPSS application. From this research, we know that from 121 respondents as Universitas Airlangga students, most of them had a moderate stress level (74%), followed by a high perceived stress level (23%), and a low level (3%). Then, the coping managements that have been done by them majority doing the problem-focused coping to adapt with the stress condition and the coping strategies that have been done in COVID-19 pandemic condition is following health protocol as the government policy.